2018
DOI: 10.1177/1591019918758493
|View full text |Cite
|
Sign up to set email alerts
|

Complications of endovascular treatment for intracranial aneurysms: Management and prevention

Abstract: Endovascular coiling for intracranial aneurysms has become an accepted treatment with good clinical results and provides adequate protection against rebleeding and rupture of aneurysms. However, despite the experience, preparation, or skill of the physician, complications during endovascular treatment still occur. The main complications of endovascular coiling are: procedural aneurysmal perforations by the microcatheter, micro-guidewire, or coil, and thromboembolic events. Such situations are unexpect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
66
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 60 publications
3
66
1
2
Order By: Relevance
“…As intraoperative complications such as aneurysm perforation or thromboembolism can have fatal consequences, safe handling of neurointerventional materials is crucial [ 14 ]. Hence, not only optimal preoperative preparation of the patient–e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As intraoperative complications such as aneurysm perforation or thromboembolism can have fatal consequences, safe handling of neurointerventional materials is crucial [ 14 ]. Hence, not only optimal preoperative preparation of the patient–e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, not only optimal preoperative preparation of the patient–e.g. adequate indication, antiplatelet therapy etc.–but moreover a well-trained physician with sufficient technical skills are pivotal factors for procedural success [ 14 ]. The improvement of technical skills by means of simulator based angiography in neurosurgery has been previously demonstrated by Fargen et al [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral infarction on DWI after neurointerventional procedure may be caused by tiny thrombi, fragmented atherosclerotic plaques, air bubbles or hydrophilic coating materials from catheters and wires during catheter insertion or injection of contrast media or flushing saline [ 12 , 13 ]. Our multivariate analysis showed a significant relationship between procedural thromboembolisms and procedural time (adjusted OR; 1.020, 95% CI; 1.002–1.039, p = 0.030).…”
Section: Discussionmentioning
confidence: 99%
“…Many literatures pointed out rate of the intraprocedural rupture of the aneurysm from endovascular treatment ranging between 1% and 5%. [ 9 16 ] This is one of the disadvantages of simple coiling when compare to balloon-assisted coiling, that using balloon can control hemorrhage after the incidence. Some studies also showed that balloon-assisted coiling do not increase rate of intra-procedural rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also showed that balloon-assisted coiling do not increase rate of intra-procedural rupture. [ 16 ]…”
Section: Discussionmentioning
confidence: 99%